MRI and PET-CT Failed to Differentiate Between Hepatic Malignancy and Brucelloma. (8th March 2018) - Schreiber, Peter W; Schmid, Adrian; Fagagnini, Stefania; Kröger, Arne; Vrugt, Bart; Reiner, Cäcilia S; Boggian, Katia; Schiesser, Marc; Müllhaupt, Beat; Günthard, Huldrych F
Abstract: Brucellosis is a common, worldwide zoonosis. Clinical presentation is protean and often goes unrecognized. Hepatic brucelloma is a rare local complication of chronic brucellosis. We report a case in which magnetic resonance imaging and positron emission tomography imaging prompted suspicion of a hepatic malignancy. Diagnosis was ultimately made by serology and polymerase chain reaction of resected liver tissue.